Hector M. Patmore – Josef Lössl (eds.), Demons in Early Judaism and Christianity . Characters and Characteristics (Ancient Judaism and Early Christianity 113; Leiden – Boston, MA: Brill 2022) - Kinowski, Krzysztof (The Biblical Annals, 2023)
Book Review: Hector M. Patmore – Josef Lössl (eds.), Demons in Early Judaism and Christianity . Characters and Characteristics (Ancient Judaism and Early Christianity 113; Leiden – Boston, MA: Brill 2022). Pp. 339. € 146.28. ISBN 978-90-04-51714-1